Trayectorias y transiciones educativas de los estudiantes mexicanos: procesos, rutas y experiencias por el sistema educativo nacional. Libro de López Ramírez y Rodríguez - Arvizu , Vanessa (El Colegio de México, 2023)
This book is composed of eight chapters by leading authors in the study of educational trajectories and transitions and aims to understand how and what factors shape and diversify academic paths during the passage between grades and educational levels. The book itself is organized as a trajectory: it begins with a chapter that addresses the transition through secondary education and ends with a paper that explores the relationship between university education and placement in the labor market. This review presents the contribution of the whole book and its chapters, based on the plurality of methodological and analytical perspectives from which educational transitions and trajectories are observed.